Study the Annealing Effect on Electrical properties of (As0.5Se0.5) doped With Tellurium - Rusul Adnan Al-Wardy (College of Pharmacy / Mustansiriyah University, 2018)
During this work, the study of electrical properties of (As0.5Se0.5 doped with 1%Te) thin films which prepared by thermal vacuum evaporation on glass substrate bases at room temperature with (100±20)nm thickness, deposition rate (1.6nm/s) and study effect of annealing at temperatures (Ta) (348,398 and448)K for (30min) on these properties. The X-ray diffraction pattern showed that all prepared films have amorphous structure. The electrical measurements explain that D.C. conductivity increases as annealing temperature (Ta) increases and all films have two values of activation energy (Ea1) and (Ea2) and found that it decrease when (Ta) increases. From study Hall effect, all samples showed (p-type) and carrier's concentration (p) increase while it's mobility decreases with increasing of (Ta). From measurements of thermoelectric power showed that the thermal activation energy (Es) smaller than the D.C. conductivity (Ea2) and (Es) decrease as (Ta) increase.